Analisis Pengaruh Budaya Organisasi dan Komitmen Beragama terhadap Loyalitas Mahasiswa di Perguruan Tinggi Islam Swasta - Syamsudin, Syamsudin (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Research about student loyalty, viewed from the perspective of marketing in educational institutions, becomes a primary focus for a university aiming to acquire a competitive edge through the number of students loyal to the institution. This study aims to explore the influence of organizational culture and religious commitment on the level of student loyalty. Although there have been numerous previous studies covering aspects of student loyalty, most of them overlook the roles played by religious commitment and organizational culture as key factors influencing loyalty levels. Therefore, this research is conducted to address gaps in the literature on student loyalty. This research employs a quantitative method and involves students from the Islamic Religious Education Study Program at one of the private Islamic universities in Yogyakarta as the research subjects. Data is collected through surveys using both primary and secondary data. Data analysis is conducted using multiple linear regression. The research findings indicate that the organizational culture does not exert a notable influence on student loyalty, while religious commitment has a significant and positive effect on the degree of student loyalty.